Cloud Computing Development of PT Divistant Teknologi Indonesia CRM System Using Microsoft Azure - Muttaqin, Husni Rofiq; Setiyadi, Angga (Universitas Komputer Indonesia, 2024)
Cloud computing technology offers modern solutions by providing integrated virtual resources, including storage and infrastructure. Based on problem identification at PT. Divistant Teknologi Indonesia, this research aims to implement cloud computing using Microsoft Azure services for the company's CRM application. The implementation includes backup and recovery integration to enhance the application's availability, security, and scalability. Research steps involve problem identification, system requirements analysis, implementation, and testing. Results show that Microsoft Azure supports backup and recovery while significantly improving performance. The case study at PT. Divistant Teknologi Indonesia demonstrates that migrating the CRM application to cloud computing meets the need for improved data availability and security, addressing issues previously encountered with shared hosting. This research positively impacts CRM performance and minimizes the risk of critical data loss, supporting smooth business operations and maintaining strong customer relationships.